Voltage Balancing Control Strategy in Converter System for Three-Level Inverters - Srinu Vaseee; B.V. Sankerram (International Journal of Electrical and Computer Engineering (IJECE), 2013)
Outcome of DC-link capacitor voltage variation on inverter switching states is accessible and designed for three-level inverter. In this paper for back-to-back system by including five-level diode clamped topologies we are proposing a novel DC link balancing method. The algorithm which we proposed here is the improvement of variable switching frequency control policy which was previously introduced by means of three-level back-to-back system which depends on calculations of adjacent capacitor voltages which focuses on three-level DC link network to identify the information about potential variation in consecutive nodes. As per the above proposal, all four capacitors in DC link network are effectively balancing the voltage. Due to optimization of switching losses the proposed method has advantages over the variable switching frequency.DOI:http://dx.doi.org/10.11591/ijece.v3i1.1471